Effect of Talking Stick Learning on Senior High School Students' Geography Achievement: Quasi-Experimental Study - Nova Yulizar; Syafri Anwar (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
Low achievement in geography learning remains a challenge at the senior high school level, partly due to teachers' ineffective implementation of instructional models. This study aims to examine the effect of the Talking Stick cooperative learning model on achievement in geography among twelfth-grade senior high school students. A quantitative approach with a quasi-experimental design was employed, involving 30 students divided into an experimental group and a control group. Data were collected using a multiple-choice achievement test and analyzed through inferential statistics. The results indicate that students taught using the Talking Stick model achieved higher average learning outcomes than those receiving conventional instruction. These findings suggest that the Talking Stick cooperative learning model effectively enhances students' achievement in geography by promoting active participation, confidence in expressing ideas, and peer interaction. This study contributes to the literature on cooperative learning by providing empirical evidence that the Talking Stick model represents a practical instructional alternative for improving the quality of geography learning in senior high schools.